Multiple Intelligence Type Profile of Prospective Physics Teacher Students: Recommendations for Lecture Methods to Create a Superior and Globally Competitive Generation - Hikmawati Hikmawati; Muhammad Taufik; Jannatin Ardhuha; Satutik Rahayu; Irman Muliadi (Kappa Journal, 2024)
The type of multiple intelligence possessed by students can be a consideration for lecturers in determining the right lecture method so that it can create effective learning. The effectiveness of learning has an impact on the quality of superior and competitive student competencies. This study aims to analyze the distribution of multiple intelligences of students and relate them to relevant learning methods in the Physics Curriculum Review course in the Physics Education Study Program, University of Mataram. The subjects of the study were 22 class 5C students who took the multiple intelligence test. This study uses a descriptive approach with quantitative data analysis. The study was conducted in August 2024. The instrument used to view the profile of students' multiple intelligence types can be accessed through the online platform "Aku Pintar". The results showed that intrapersonal intelligence had the highest average of 83%, followed by logical-mathematical intelligence (78%), visual-spatial (75%), and verbal-linguistic (73%). Naturalistic and Interpersonal intelligence were 71%, while Kinesthetic intelligence was 70%. Musical intelligence had the lowest average, which was 63%. Based on these findings, the recommended learning methods include Project-Based Learning, Small Group Discussion, Contextual Instruction, and Role-Play to accommodate various types of student intelligence. These methods are integrated with topics such as the history of curriculum development, review of learning models, review of the Independent Curriculum teaching module, and the Pancasila Student Profile Strengthening Project. The conclusion of the study emphasizes the importance of implementing adaptive and varied learning methods in supporting the potential of students' multiple intelligences, in order to prepare them as competent, creative, and innovative prospective teachers. In other words, the application of lecture methods used by lecturers according to the type of multiple intelligences of students will support the formation of a superior and globally competitive generation. It is recommended for lecturers to optimize project-based and collaborative approaches, and for students to actively explore their intelligence potential. This study also provides recommendations to study programs to align the curriculum with student needs and educational developments.